QUALITY OF SERVICE OF OUTPATIENT UNIT IN BA HOSPITAL, INDONESIA - Suvonalya Suvonalya; Adang Bachtiar (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: The quality of healthcare services is crucial in the healthcare service organization to encourage every healthcare service organization to improve their healthcare service quality. This study aims to identify the description of the service quality of outpatient department in RSBA, East Jakarta, DKI Jakarta, Indonesia using the criteria of Malcolm Baldridge. Method: This research was a descriptive analytical study with cross-sectional study combined with qualitative and quantitative approaches (mix method). About 110 respondents were selected as sample. The data analysis employed were univariate, bivariate and multivariate analysis of multiple logistic regression test conducted by using SPSS statistic software for Windows. Result : There was a significatt influence of on workforce, and last focus on process and focus on the service quality of outpatient department of RSBA with p-value of < 0.05 and 9. In multiple logistic regression tests, the factors that had strong closeness were the leadership and the measurement analysis and knowledge management. Conclusion : The Healthcare quality of the outpatient department of RSBA needed improvement, especially on the focus on the customers and the process. The commitment of all elements in the hospital was requried. The well and correct service customers, appropriate to the medical treatment according to the standard operating procedures, the excellent service and the effort to meet the completeness of the hospital infrastructure were important aspects that should be undergone by RSAB to improve the hospital’s service quality.